Architecture of the outer-membrane core complex from a conjugative type IV secretion system - Himani Amin (Nature Portfolio, 2021)
DNA transfer between two bacterial cells is mediated by the conjugative type 4 secretion systems (T4SSs). Here, the authors report the structure of a complete T4SS outer-membrane core complex (OMCC), revealing distinct C17 and C13 symmetries of its central inner and peripheral outer ring regions, respectively.